Topological search of the crack pattern from a continuum mechanical computation. (15th September 2015) - Bottoni, Marina; Dufour, Frédéric; Giry, Cédric
Highlights: The purpose of the presented algorithm is to retrieve the crack path out of a continuum numerical model. The algorithm is the first step of a larger procedure aiming at retrieving the crack opening and computing leakage. The algorithm finds the ridges of the geometrical space generated by damage or an equivalent scalar variable. The algorithm is applied successfully to two examples. Retrieving crack paths helps to assess convergence of the damage model upon mesh refinement by comparing crack paths. Abstract: In this contribution, a method to track the crack path from a continuum finite element simulation using failure material models is presented. The work belongs to a larger project, aiming at extracting the crack opening a posteriori of a continuum finite element computation to deal with durability assessment of concrete structures. Cracking is modelled in a diffuse manner by a distribution of an appropriate scalar state variable associated to material degradation. With the proposed method, the crack path is found in the post-processing phase by means of a step-by-step procedure. At each step, a new location point is computed where the state variable is maximum in a given direction at a given distance. Furthermore a specific procedure is proposed to detect multiple cracks in an automatic way. The proposed method is successfully applied to two studies implying either a single crack or a multi-crack pattern, obtained with different continuum models to highlight the versatility of the proposed approach.